Survival guide to general chemistry - McMahon, Patrick E.; McMahon, Rosemary Fischer; Khomtchouk, Bohdan B. (Boca Raton, Florida : CRC Press, 2019)
This work evolved over thirty combined years of teaching general chemistry to a variety of student demographics. The focus is not to recap or review the theoretical concepts well described in the available texts.Instead, the topics and descriptions in this book make available specific, detailed step-by-step methods and procedures for solving the major types of problems in general chemistry. Explanations, instructional process sequences, solved examples and completely solved practice problems are greatly expanded, containing significantly more detail than can usually be devoted to in a comprehensive text. Many chapters also provide alternative viewpoints as an aid to understanding. Key Features: The authors have included every major topic in the first semester of general chemistry and most major topics from the second semester. Each is written in a specific and detailed step-by-step process for problem solving, whether mathematical or conceptual Each topic has greatly expanded examples and solved practice problems containing significantly more detail than found in comprehensive texts Includes a chapter designed to eliminate confusion concerning acid/base reactions which often persists through working with acid/base equilibrium Many chapters provide alternative viewpoints as an aid to understanding This book addresses a very real need for a large number of incoming freshman in STEM fields
VI: Answers to Practice ProblemsChapter 6: Procedures for Calculating Empirical and Molecular Formulas; I: General Concept; Concepts of Empirical or Molecular Formulas; II: Procedure for Calculation of Simplest (Empirical) Formula of Any Compound; III: Determination of the Simplest Formula from Element Mass Percent; IV: Determination of the True Molecular Formula for Molecules; Determining and Using the Multiple; Procedure for Finding the Simplest Formula and True Molecular Formula; V: Experimental Determination of Compound Formulas; VI: Practice Problems; VII: Answers to Practice Problems
OCLC-licensed vendor bibliographic record.
Keywords: Chemistry, Organic -- Textbooks; SCIENCE / Chemistry / Organic; SCIENCE / Chemistry / General; MEDICAL / Biochemistry